2000
DOI: 10.1016/s0735-1097(99)00627-0
|View full text |Cite
|
Sign up to set email alerts
|

Expiratory flow limitation as a determinant of orthopnea in acute left heart failure

Abstract: Expiratory FL appears to be common in patients with acute LHF, particularly so when orthopnea is present. Its postural aggravation could contribute to LHF-related orthopnea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0
6

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(47 citation statements)
references
References 37 publications
2
39
0
6
Order By: Relevance
“…Lung mechanics at rest are within the predicted normal range, except for a mild reduction in VC, FEV1 and in end-expiratory airflow, as described previously [19]. During lung function and exercise testing, the supine position was avoided, since this position induced an increase in airflow resistance, an aggravated expiratory flow limitation and a decrease in lung compliance in patients with left ventricular failure [20][21][22]. In IPAH patients, the effects of assuming a supine position have not been investigated so far.…”
Section: Patients' Characteristicsmentioning
confidence: 58%
“…Lung mechanics at rest are within the predicted normal range, except for a mild reduction in VC, FEV1 and in end-expiratory airflow, as described previously [19]. During lung function and exercise testing, the supine position was avoided, since this position induced an increase in airflow resistance, an aggravated expiratory flow limitation and a decrease in lung compliance in patients with left ventricular failure [20][21][22]. In IPAH patients, the effects of assuming a supine position have not been investigated so far.…”
Section: Patients' Characteristicsmentioning
confidence: 58%
“…The effect of posture on lung function is also important. Studies have shown increased flow limitation in patients with both acute 21, 22 and chronic, stable HF 23 when placed in the supine position. This is likely to be caused by fluid shift from the lower limbs into the lung and upper airway resulting in increased airway resistance.…”
Section: Effects Of Hf On Respiratory Function Testingmentioning
confidence: 99%
“…In conclusion, the NEP technique has been used clinically in studies with the following: 1) COPD (during mechanical ventilation and exercise, correlation with dyspnoea, orthopnoea, and other lung function indexes, before and after bronchodilatation, various postures) [22-25, 27, 33, 42, 43, 49, 50]; 2) asthma (stable asthma, during MCh bronchocostriction, and during exercise) [28,[44][45][46]; 3) cystic fibrosis [52,53] and bronchiectasis [54]; 4) restrictive lung disease [33,37]; 5) obesity [32,55,56]; 6) mechanically ventilated with acute respiratory failure and ARDS [7,8,23,[30][31][32]; 7) left heart failure [57]; 8) after single lung transplantation [29,58]; 9) euthyroid goitre [59]; and 10) assessment of bronchial hyperreactivity [60]. It appears that the use of the NEP technique during tidal flow-volume analysis studies has led to the realisation of the important role of EFL in exertional dyspnoea and ventilatory impairment for a surprisingly wide range of clinical circumstances [61].…”
Section: Clinical Applicationsmentioning
confidence: 99%